Governing for the future designing democratic institutions for a better tomorrow - Boston, Jonathan, 1957- (Bingley, U.K. : Emerald, 2016)
This book is about governing well for the future. It investigates the nature of, and the conditions for, prudent long-term democratic governance in a dynamic, complex, and uncertain world, the reasons why such governance is politically challenging, and how such challenges can best be tackled. In particular, it addresses the problem of 'short-termism' or a 'presentist bias' in policy-making; that is, the risk of governments placing undue weight on near-term considerations at the expense of a society's overall long-term welfare. As such, the book traverses both normative and empirical issues. The approach is primarily qualitative rather than quantitative.
Intertemporal policy-making in advanced democracies: the risk of a presentist bias -- The presentist bias: conceptualizing and assessing the problem -- Probing the causes of the presentist bias -- The policy dimensions of the presentist bias -- Foundations for prudent long-term governance -- Countering the presentist bias: surveying the options -- A constitution for the future -- Committing to a better future - the nature, design, and limits of commitment devices -- Insulating decision-making from short-term political pressures -- Enhancing voices for the future - the role of independent institutional advocates and guardians -- Advising for a better future - evidence, metrics, frameworks, and institutions -- Designing and embedding a strategic foresight capability -- Creating the political conditions for policy investments: enhancing trust, shared goals, and patience -- Towards a better tomorrow - enhancing the capacity of advanced democracies to navigate, shape, and protect the future.
Includes index.
Includes bibliographical references.
Print version record
Keywords: Political Science -- Public Policy / Regional Planning; Corporate governance & responsibilities; Democracy; Policy sciences; Public administration